2014
DOI: 10.1111/apt.12699
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: faecal microbiota transplantation therapy for digestive and nondigestive disorders in adults and children

Abstract: SUMMARY BackgroundThere has been growing interest in the use of faecal microbiota transplantation (FMT) for the treatment of gastrointestinal and nongastrointestinal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
109
0
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 99 publications
4
109
0
15
Order By: Relevance
“…In this study, 83.3% were cured with only one administration, these results being similar to those reported in the literature (13). However, a patient required three FMTs to resolve diarrhea, which highlights the fact that some patients will require more than just one procedure to achieve remission.…”
supporting
confidence: 89%
“…In this study, 83.3% were cured with only one administration, these results being similar to those reported in the literature (13). However, a patient required three FMTs to resolve diarrhea, which highlights the fact that some patients will require more than just one procedure to achieve remission.…”
supporting
confidence: 89%
“…125 Another review found similar results, with 78% of patients, both pediatric and adult, achieving remission. 126 However, these studies only included data from case reports or series, which are not controlled and subject to publication bias. A more recent systematic review which included a randomized trial for FMT in IBD noted less promising results, with 45% of patients achieving remission (22% of patients with UC, 60.5% of patients with CD).…”
Section: Systematic Reviews Of Fmt In Ibdmentioning
confidence: 99%
“…Given the success of FMT in this one area, and given the appeal and curiosity exhibited by providers and the lay public, it is not surprising, that consideration of FMT for other conditions associated with disturbances of the microbiome is under active discussion (14).…”
mentioning
confidence: 99%